Um estudo da ironia em crônicas contemporâneas e sua contribuição para o ensino de língua portuguesa - Cruz, Eliane das Dores Martins da (2024)
Approaching irony in the school environment, in the light of Cognitive Linguistics, is essential to boost and enrich research on language use. Irony, like metaphor and metonymy, is a phenomenon present in various interactions, transcending specific areas and permeating activities of human knowledge. Thus, in this research the goal is to explore irony as a relevant mechanism for teaching Portuguese language, from a linguistic-cognitive and also pragmaticdiscursive perspective. Regarding the methodology, this research was done through a qualitative approach. Initially, several theoretical studies on irony were carried out. Subsequently, we analyzed six chronicles by three contemporary writers: Arnaldo Jabor, Antônio Prata and Millôr Fernandes. The results show that the manifestation of irony in the chronicles, in general, has a critical function in defending a point of view. To construct critique, resources such as humor, exaggeration and the creation of unusual scenarios are used, which are normally dissociated from the expectations and standards established as recurring in the socio-physical world. In view of the argumentative and critical function of irony, it can be a relevant instrument in the development of reading practice in the classroom